Osmanlı İdaresinde Kıbrıs’ta Serkis Ağa Liderliğindeki Bir Ermeni Tercüman Ailesi ve Faaliyetleri - Ali Efdal ÖZKUL (Gazi Akademik Bakış)
Due to its particular location in the Eastern Mediterranean, Cyprus has since the earliest historical periods attracted the attention of many civilizations and societies aiming at domination in the region. Consequently, since the ancient times Cyprus has been in different ways placed in the routes of the communities being active in the Mediterranean. The Armenian presence in Cyprus could be traced back to the 6th century and the Eastern Roman Empire. It is well known that Armenians in the Ottoman Empire were predominantly engaged in trade. Therefore, it is very unlikely to consider a possibility that the Armenian community in its commercial activities could have excluded a place like Cyprus assuming a crucial role in the Eastern Mediterranean trade. Accordingly, trade was also the main activity of the Armenian community settled in Cyprus. The Cypriot Armenians were mostly engaged in island’s silk production and its commercial distribution. Additionally, some merchants from the Armenian community were also employed as translators for the foreign consuls assigned to Cyprus (in particular French, British and Dutch). One of the Armenian residents in Cyprus was a merchant named Sarkis, son of Avak. In addition to commercial activities, Sarkis occasionally served as a translator for French and British consulates. From the archival sources we can conclude that also other members of Sarkis’ family were engaged in different times as translators for different consulates. The paper aims to offer an account of commercial and other activities of the members of the family, in particular Sarkis, son of Avak himself, in Cyprus. The research was based on the Ottoman court registers from Nicosia, Cyprus, as well as the domestic and foreign archival sources preserved in Presidential Ottoman Archives, Republic of Turkey. The result of the research is a survey of positive and negative contributions of the activities of Sarkis, a prominent member of the Armenian community in Cyprus, as well as his family, to the political, social, and economic life of the island.